Techniques to Enhance Solubility of Hydrophobic Drugs: An Overview - Vimalson, D. Christopher (Asian Journal of Pharmaceutics (AJP), 2016)
The solubility enhancement process of hydrophobic drugs plays a key role in the formulation development to achieve the bioavailability and therapeutic action of the drug at the target site. About 40% of the new chemical entities identified by pharmaceutical industry screening programs face numerous problems in the formulation and development stage because of poor water solubility and low bioavailability. Drug solubility and bioavailability enhancement are the important challenges in the field of formulation of pharmaceuticals. The Biopharmaceutics Classification System reflects that Class II and IV drugs have low water solubility, poor dissolution, and low bioavailability. This review article explores the various techniques to enhance solubility of hydrophobic drugs such as complexation of drugs, use of cosolvents, emulsion formation, microemulsions, micelles, polymeric micelles, pharmaceutical salts, pro-drugs, particle size reduction technologies, solid state alternation, soft gel technology, solid dispersion techniques, drug nanocrystals, nanomorph technology, and crystal engineering techniques.